Never saw it coming : cultural challenges to envisioning the worst - Cerulo, Karen A. (University of Chicago Press, 2006)
People?especially Americans?are by and large optimists. They're much better at imagining best-case scenarios (I could win the lottery!) than worst-case scenarios (A hurricane could destroy my neighborhood!). This is true not just of their approach to imagining the future, but of their memories as well: people are better able to describe the best moments of their lives than they are the worst. Though there are psychological reasons for this phenomenon, Karen A. Cerulo, in Never Saw It Coming, considers instead the role of society in fostering this attitude. What kinds of communities develop this.